2016
DOI: 10.1007/s00167-016-4153-7
|View full text |Cite
|
Sign up to set email alerts
|

Articular cartilage status 2 years after arthroscopic ACL reconstruction in patients with or without concomitant meniscal surgery: evaluation with 3.0T MR imaging

Abstract: Prospective comparative study, Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…1 A previous study of 29 patients with follow-up MRI at 2 years demonstrated similar findings of tricompartmental cartilage loss after ACLR, with an increased risk of cartilage loss after medial meniscal surgery, although that study was too small to clearly delineate the findings of lateral meniscectomy. 14 The primary outcome was the cartilage damage score (CDS), with each subregional score determined by computing the score for the ipsilateral knee minus the score for the contralateral knee and summed for the compartment or whole joint. A positive value for the CDS indicates that the reconstructed knee has more cartilage damage than the contralateral healthy knee.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 A previous study of 29 patients with follow-up MRI at 2 years demonstrated similar findings of tricompartmental cartilage loss after ACLR, with an increased risk of cartilage loss after medial meniscal surgery, although that study was too small to clearly delineate the findings of lateral meniscectomy. 14 The primary outcome was the cartilage damage score (CDS), with each subregional score determined by computing the score for the ipsilateral knee minus the score for the contralateral knee and summed for the compartment or whole joint. A positive value for the CDS indicates that the reconstructed knee has more cartilage damage than the contralateral healthy knee.…”
Section: Discussionmentioning
confidence: 99%
“…1 A previous study of 29 patients with follow-up MRI at 2 years demonstrated similar findings of tricompartmental cartilage loss after ACLR, with an increased risk of cartilage loss after medial meniscal surgery, although that study was too small to clearly delineate the findings of lateral meniscectomy. 14…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cartilage degeneration at different sites of the knee occurs after anterior cruciate ligament reconstruction (ACL-R) [ 9 , 14 , 23 ]. Older age, higher body mass index (BMI), meniscal tears, and technical errors may accelerate cartilage degeneration after primary ACL-R [ 11 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accompanying meniscal injury has been the most commonly reported risk factor for OA development following ACLR [1]. Evaluating articular cartilage changes after a 2-year follow-up in patients who underwent arthroscopic ACLR with or without concomitant meniscal surgery, Michalitsis et al reported more chondral defects in the group that underwent partial meniscectomy at the time of arthroscopic ACLR [10].…”
Section: Introductionmentioning
confidence: 99%